The hotel guest : a novel - Hennigan, Rosemary (Park Row Books, 2026)
"Kit's summer position at the Abbaye de Saint Maurice, an upscale hotel in the French Alps, was meant to be a new start. But after she became entangled with a mysterious group of guests, the estate came to hold her darkest secret, which left her with no choice but to flee. After a decade spent laying low, Kit receives an invitation to return to the hotel. But who is calling her back? And why, when they all promised to stay away? Kit can't resist the pull of the Abbaye and the chance to finally find closure. But upon arrival, she learns that a former flame is writing a book that could expose the group's shared secret. The others need her help to stop him, but will Kit be able to betray the man she once loved for the good of the rest? And how far are her old friends willing to go to protect themselves? When new details surface about that long ago summer, Kit is forced to question the story she's been telling herself, about its disturbing ending, and what it all says about the person she really is."--Amazon.